Boesenbergia rotunda (L.). Mansfeld: Manfaat dan Metabolit Sekundernya - Marina Silalahi (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2017)
Boesenbergia rotunda (L.). Mansfeld, or temu kunci is native plant in Indonesia, which is used as medicine, vegetables, and spices. The use of plants as medicine and spices relates to its compounds of secondary metabolites. This article aims to explain the uses and bioactive compounds of B. rotunda. This article is based on literature offline and online media. Offline literature used the books, whereas online media used Web, Scopus, Pubmed, and scientific journals. Boesenbergia rotunda have flavonoids (chalcones, flavanones, and flavones) and essential oils (terpinene, geraniol, camphor, Î±-ocimene, 1,8-cineole, myrcene, borneol, camphene, methyl cinnamate, terpineol, geranial, and neral. The essential oil founded on B. rotunda produces a distinctive odour, so that are used as antipyretic, aroma theraphy, and analgesic. Flavonoids of B. rotunda have been used as an anti-HIV-1, antitumor, anti-inflammatory, anti-oxidative, anti-cancer, anti-obesity, and anti-microbial. Extract of B. rotunda resulted lysis of membranes and walls microbial. The uses of extract of B. rotunda as antiobesity because its to increase the activity of enzymes involved in lipid catabolism. Keywords: Boesenbergia rotunda, essential oils, flavonoids, anti-microbial